A Review of SPSS 12.01, Part 2. - Hilbe, Joseph M. (American Statistician, 2004)
A review of the statistical software package SPSS version 12. 01 is presented. The writer contends that it is a first-rate statistical software package, suited to the needs of most researchers and statisticians.